Exploring the Economic and Social Determinants of Psychological and Psychosocial Health - Michael A. Shields; Stephen Wheatley Price (Institute for the Study of Labor (IZA), 2001)
This paper explores the determinants of individuals? psychological and psychosocial health using recent Health Survey for England data. We find evidence that our dependent variables, defined, respectively, from the GHQ12 and Perceived Social Support scores, are negatively related to household poverty as well as acute and chronic physical health. Unemployment has a detrimental effect for both men and women, but this effect is mitigated for individuals residing in high employment deprivation areas, suggesting a ?social norm? effect. Our random effects (household) ordered probit modelling approach finds that unobserved intra-household characteristics play an important role in determining an individual?s levels of psychological and psychosocial health.
Keywords: I3; I1; 330; Psychological health; psychosocial health; deprivation; intra-household effects; social norm; unemploymenteffects; Psychische Störung; Armut; Arbeitslosigkeit; Soziale Werte; Schätzung; Großbritannien